Aggressive elites and vulnerable entrepreneurs: Trust and cooperation in the shadow of conflict - Halvor Mehlum; Karl Ove Moene (University of Oslo, Department of Economics, 2010)
We explore the implications of having a divided society where group leaders have motives for aggression towards other groups but where entrepreneurs have a desire for cooperation and peace. We assert that it is members of the elites who start conflicts and wage wars while the entrepreneurs undertake the type of economic activities that they find most profitable given the circumstances. We derive implications for peace and conflict. We find conflict induced poverty traps with self-fulfilling expectations about conflict and we derive implications for peace building strategies.
Keywords: C73; D72; D74; 330; Conflict; investments; trust; cooperation; Gesellschaft; Elite; Konflikt; Unternehmer; Kooperation; Vertrauen; Wohlfahrtseffekt